Adipose tissue expansion: impact on insulin sensitivity, β-cell function, liver function and cardiovascular health. European Group for the Study of Insulin Resistance (EGIR) annual scientific meeting; Pisa, Italy; 12–14th May 2016. (October 2016) - Petrie, John
Abstract : The 25th annual European group for the study of insulin resistance (EGIR) was recently held in Pisa, Italy. The discussions centred around the impact of adipose tissue on insulin sensitivity, β-cell function, liver function and cardiovascular health.